Proteome changes in a human retinal pigment epithelial cell line during oxidative stress and following antioxidant treatment - Duncan, R. Scott; Keightley, Andrew; Lopez, Adam A.; Hall, Conner W.; Koulen, Peter (Frontiers in Immunology, 2023)
Purpose: Age related macular degeneration (AMD) is the most common cause of blindness in the elderly. Oxidative stress contributes to retinal pigment epithelium (RPE) dysfunction and cell death thereby leading to AMD. Using improved RPE cell model systems, such as human telomerase transcriptase-overexpressing (hTERT) RPE cells (hTERT-RPE), pathophysiological changes in RPE during oxidative stress can be better understood. Using this model system, we identified changes in the expression of proteins involved in the cellular antioxidant responses after induction of oxidative stress. Methods: Some antioxidants such as vitamin E (tocopherols and tocotrienols) are powerful antioxidants that can reduce oxidative damage in cells. Alpha-tocopherol (αT) and gamma-tocopherol (γT) are well-studied tocopherols, but signaling mechanisms underlying their respective cytoprotective properties may be distinct. Here, we determined what effect oxidative stress, induced by extracellularly applied tBHP in the presence and absence of αT and / or γT, has on the expression of antioxidant proteins and related signaling networks. Using proteomics approaches, we identified differential protein expression in cellular antioxidant response pathways during oxidative stress and after tocopherol treatment. Results: We identified three groups of proteins based on biochemical function: glutathione metabolism/transfer, peroxidases and redox-sensitive proteins involved in cytoprotective signaling. We found that oxidative stress and tocopherol treatment resulted in unique changes in these three groups of antioxidant proteins indicate that αT and γT independently and by themselves can induce the expression of antioxidant proteins in RPE cells. Conclusions: These results provide novel rationales for potential therapeutic strategies to protect RPE cells from oxidative stress.